2007
DOI: 10.1021/es0716352
|View full text |Cite
|
Sign up to set email alerts
|

Toxicogenomic Analysis Provides New Insights into Molecular Mechanisms of the Sublethal Toxicity of 2,4,6-Trinitrotoluene in Eisenia fetida

Abstract: Xenobiotics such as explosives and pesticides released into the environment can have lethal and sublethal impacts on soil organisms such as earthworms with potential subsequent impacts at highertrophic levels. To better understand the molecular toxicological mechanisms of 2,4,6-trinitrotoluene (TNT), a commonly used explosive, in Eisenia fetida, earthworms were exposed to a gradient of TNT-spiked soils for 28 days and impacts on gene expression were examined using a 4032 cDNA microarray. Reproduction was incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 48 publications
5
49
0
1
Order By: Relevance
“…We used the filter paper contact test because it offers a prompt and easy method for screening chemicals potentially toxic to earthworms under strictly standard exposure conditions (Roberts and Dorough 1984;Robidoux et al 2002;Gastaldi et al 2007;Gong et al 2007). Renoux et al (2000) using this contact test found that earthworms of the species Eisenia andrei absorb TNT through the body wall, even after a very short contact (about 5 min).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the filter paper contact test because it offers a prompt and easy method for screening chemicals potentially toxic to earthworms under strictly standard exposure conditions (Roberts and Dorough 1984;Robidoux et al 2002;Gastaldi et al 2007;Gong et al 2007). Renoux et al (2000) using this contact test found that earthworms of the species Eisenia andrei absorb TNT through the body wall, even after a very short contact (about 5 min).…”
Section: Discussionmentioning
confidence: 99%
“…To narrow down the range for contaminants prior to soil testing and for the comparison of different biomarkers, the filter paper contact test could be a simple and inexpensive research tool (Roberts and Dorough 1984;Robidoux et al 2002;Gastaldi et al 2007;Gong et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…These studies typically have relied on model organisms, either directly or indirectly, in which established genetic, functional, or metabolic pathways have been characterized in detail. A few recent examples include the investigation of the mode of action for hepatotoxicity of triazole fungicides in rats [12], mapping of genes to functional pathways of model animals enabling investigation of the mode of action of explosives in fathead minnows, earthworms, and bobwhite quail [13][14][15], and metals and ibuprofen in Daphnia magna [16,17]. Several strategies for characterizing chemicals with unknown modes of action have been proposed, using classification models created from gene expression profiles of chemicals with known modes of action [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…To date, fish, particularly zebrafish and fathead minnow, and Daphnia magna, appear to be the most common model organisms for ecotoxicogenomics studies employing DNA microarrays. Nonetheless, there are a few rare examples of studies conducted with birds (e.g., Yeung et al, 2007), amphibians (Helbing et al, 2007a,b;Page et al, 2007), mussels (Dondero et al, 2006), and terrestrial invertebrates (Gong et al, 2007(Gong et al, , 2008Bundy et al, 2008). Additionally transcriptomic methods have been used to study the effects of contaminants and other environmental stressors on phytoplankton (Chlamydomonas reinhardtii ;Jamers et al, 2006) and corals Morgan et al, 2005).…”
Section: The Practice Of Ecotoxicogenomics: Transcriptomicsmentioning
confidence: 99%